IDENTIFIKASI KETIDAKBERATURAN STRUKTUR DAN KONTROL STABILITAS GEDUNG SEKOLAH KATEGORI RISIKO IV BERDASARKAN SNI 1726:2019 - Wahyu Mahendra Trias Atmadja; Hence Michael Wuaten; Hendrika Tharob (Bajang Institute, 2026)
Structural irregularities are a primary cause of seismic damage, making their identification essential for buildings classified as Risk Category IV. This study identifies the horizontal and vertical irregularities and evaluates the stability of the four-story reinforced concrete building of SMA Negeri 14 Samarinda (Special Moment Resisting Frame, fc' = 25 MPa, site class SD). A three-dimensional model was analyzed in ETABS v.20 using response-spectrum analysis following SNI 1726:2019; modal mass participation, torsional irregularity, diaphragm discontinuity, soft story, mass irregularity, the P-Delta stability coefficient, and inter-story drift were evaluated. The results reveal a type 1a torsional irregularity at the first story in both directions (ratio 1.246 in X and 1.215 in Y) and a mass irregularity at the third and fourth stories, requiring dynamic rather than equivalent-static analysis. Conversely, the structure is free of diaphragm discontinuity, soft story, and vertical geometric irregularity. The P-Delta stability coefficient remained below the maximum at all stories, and inter-story drift stayed within the 0.01·hsx limit. The findings show the building remains stable despite the detected irregularities, and underline the importance of irregularity screening in performance-oriented evaluation of educational facilities.